2007
DOI: 10.2119/2007-00113.zhou
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin and Adrenomedullin Binding Protein-1 Protect Endothelium-Dependent Vascular Relaxation in Sepsis

Abstract: Downregulation of vascular endothelial constitutive nitric oxide synthase (ecNOS) contributes to the vascular hyporesponsiveness in sepsis. Although coadministration of the potent vasodilatory peptide adrenomedulin (AM) and the newly discovered AM binding protein (AMBP-1) maintains cardiovascular stability and reduces mortality in sepsis, it remains unknown whether AM/AMBP-1 prevents endothelial cell dysfunction. To investigate this possibility, we subjected adult male rats to sepsis by cecal ligation and punc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…This finding fits with Gupta et al reporting that the salutary effect of activated protein C in rats was not associated with complete reversal of the LPS-induced increase in blood NO and ADM levels [ 15 ]. It is tempting to speculate that HAM1101 attenuated excess NO and ADM formation rather than completely blocking it while maintaining the constitutive production necessary for organ homoeostasis [ 9 , 12 ]. Clearly, the attenuated iNOS activation is not mirrored by reduced NO 2 − + NO 3 − levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding fits with Gupta et al reporting that the salutary effect of activated protein C in rats was not associated with complete reversal of the LPS-induced increase in blood NO and ADM levels [ 15 ]. It is tempting to speculate that HAM1101 attenuated excess NO and ADM formation rather than completely blocking it while maintaining the constitutive production necessary for organ homoeostasis [ 9 , 12 ]. Clearly, the attenuated iNOS activation is not mirrored by reduced NO 2 − + NO 3 − levels.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenomedullin (ADM) has been referred to as a double-edged sword in sepsis [ 1 ]: during cecal ligation and puncture (CLP)- [ 2 4 ], endotoxin- [ 5 ], or Staphylococcus aureus α-toxin-induced sepsis [ 6 ], ADM administration restored organ perfusion during the hypodynamic shock phase. This effect coincided with attenuated systemic inflammation [ 7 ], decreased activation of the inducible nitric oxide synthase (iNOS) and peroxynitrite formation [ 8 ], and reduced organ dysfunction [ 9 ], apoptosis [ 10 ], and mortality [ 6 ]. ADM release is therefore referred to as a protective adaption to systemic inflammation [ 11 ] and circulatory shock [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to endothelium-dependent vascular relaxation, AM is known to induce vasodilation which is mediated partially by endothelium-derived nitric oxide [ 92 - 96 ]. Also, in a rat model of sepsis induced by cecal ligation and puncture, administration of AM and AM-binding protein (AMBP-1 also known as complement factor H) were shown to prevent against endothelial cell dysfunction and decreased endothelium-dependent vascular relaxation in thoracic aorta [ 97 ]. These studies implicate AM as having a protective role in cardiovascular disease and endothelial dysfunction, but further research needs to be performed to investigate how AM directly impacts cardiac endothelial cells to regulate their function.…”
Section: Physiology and Pathologymentioning
confidence: 99%
“…In addition, studies have shown that downregulation of vascular endothelial constitutive nitric oxide synthase (ecNOS) contributes to vascular hyporesponsiveness in sepsis 28 . In this regard, we have previously shown that acetylcholine induced vascular relaxation was significantly reduced in late sepsis, i.e., 20 h in a rat model of cecal ligation and puncture (CLP) 29 . Gene and protein expression of ecNOS in aortic and pulmonary tissues were downregulated in late sepsis.…”
Section: Discussionmentioning
confidence: 99%